Efficient Audio Steganography Using Bit Comparison and Substitution Algorithms for Improved Embedding Capacity - Revathi, K; Mohideen, S. Kaja; Tamilselvan, Latha (Informatica, 2025)
Steganography conceals information, with audio files increasingly used in this practice. The Least Significant Bit algorithm in audio steganography requires numerous samples to embed text files effectively. This study proposes an efficient methodology for embedding text files into a digital audio file. The approach also involves embedding the index value of an audio file, which contains hidden text files in another digital audio file. The proposed algorithms are the Bit Comparison and Substitution Algorithm for embedding text files in audio files and the Bit Comparison and Retrieval Algorithm for extracting text files from audio files. Additionally, a Least Significant Bit Algorithm with a secret key (Ks) embeds the index value of the audio file. The proposed algorithm achieves an average mean squared error of 0.0513, a peak signal-to-noise ratio of 41.13732041dB, and a bit error rate of 0.000114 for embedding 2400 bytes of text files in audio files. These performance metrics demonstrate that the proposed algorithm quantitatively outperforms the traditional least significant bit algorithm by requiring fewer audio samples to embed text files. The proposed algorithm embeds 2400 bytes of text into 2400 audio samples, with each byte corresponding to a single audio sample. Each byte of the text file is embedded by modifying one bit per audio sample, resulting in 2400 difference bits between audio and stego audio files.